Sangka-Ku-Riang: Dekonstruksi Estetik Riak Ego dan Krisis Identitas dalam Ambiguitas Mozaik Digital : Mitologi Sangkuriang Generasi Moderen - Deden Maulana; I Made Gede Arimbawa; Anak Agung Gde Bagus Udayana; I Wayan Sujana (Universitas Budi Luhur, 2026)
Ancient mythologies of the Indonesian archipelago are frequently positioned as static didactic narratives. This study aims to recontextualize the legend of Sangkuriang into a new media art platform through an interactive digital mosaic installation. Employing a qualitative, practice-led research methodology, the name